Development of the Implementation of Inheritance Division from the Patrilineal Kinship System to the Parental Kinship System in Customary Law in Maubesi Village, Rote Tengah District, Rote Ndao Regency - Toumeluk, Dean Monica; Agustinus Hedewata; Darius Mauritsius (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This writing aims to examine the inheritance law system in Indonesia based on its regional nature which is closely related to the scope of human life. This writing uses a qualitative approach method with data collection measuring tools using observation and structured interviews. The sampling technique used in this writing is a saturated sample. The data source used is primary data from interviews with 17 informants who are Traditional Elders, Prospective Heirs and Heirs in one of the villages in Rote Ndao district. The results of the research concluded that the application of customary inheritance law in the patrilineal kinship system in Rote Ndao Regency has changed due to economic development. Obstacles to inheritance division disputes have experienced a change in the method of resolution, from a negotiation system to a deliberation/consensus system to reconcile the disputing parties implemented by the Village Traditional Institution and the Village Government